The Lack of Association Between Bacille Calmette-Guerin Vaccination and Clustering of Aboriginals with Tuberculosis in Western Canada. Issue 3 (3rd April 2005) - Cook, Victoria J; Hernández-Garduño, Eduardo; Kunimoto, Dennis; Hershfield, Earl S; Fanning, E Anne; Hoeppner, Vernon H; Elwood, R Kevin; FitzGerald, J Mark; Canadian Molecular Epidemiology of Tuberculosis Study Group,
Abstract : BACKGROUND: Tuberculosis (TB) remains a major health problem for Aboriginal people in Canada, with high rates of clustering of active TB cases. Bacille Calmette-Guérin (BCG) vaccination has been used as a preventive measure against TB in this high-risk population. OBJECTIVE: The study was designed to determine if BCG vaccination in Aboriginal people influenced recent TB transmission through an analysis of the clustering of TB cases. METHODS: A retrospective analysis of all culture-positive Mycobacterium tuberculosis cases in Aboriginal people in western Canada (1995 to 1997) was performed. Isolates were analyzed using standard methodology for restriction fragment length polymorphism and spoligotyping. RESULTS: Of 256 culture-positive Aboriginal TB cases, BCG status was confirmed in 216 (84%) cases; 34% had been vaccinated with BCG, 57% were male and 56% were living on-reserve. Patients who had been vaccinated with BCG were younger than unvaccinated individuals (mean age 32.4±1.65 years versus 45.0±1.8 years, P<0.0001). Clustering was found in 62% of cases: 59% of non-BCG vaccinated cases were clustered versus 68% of those vaccinated with BCG (P=0.16). Younger patients (younger than 60 years of age) were more likely to be clustered in the univariate analysis (P<0.01). When age, sex, province, and HIV and reserve status were controlled for, BCG vaccination was not associated with clustering (OR 1.3, 95% CI 0.7 to 2.6). CONCLUSIONS: BCG vaccinated Aboriginal people were no less likely to have active TB from recently transmitted disease. BCG vaccination appears to have limited value in preventing clustering of TB cases within this high-risk community.